Multifunctional Effects of Mangosteen Pericarp on Cognition in C57BL/6J and Triple Transgenic Alzheimer's Mice. (1st December 2014) - Huang, Hei-Jen; Chen, Wei-Lin; Hsieh, Rong-Hong; Hsieh-Li, Hsiu Mei
Abstract : Mangosteen- ( Garcinia mangostana -) based nutraceutical compounds have long been reported to possess multiple health-promoting properties. The current study investigated whether mangosteen pericarp (MP) could attenuate cognitive dysfunction. First, we found that treatment with MP significantly reduced the cell death and increased the brain-derived neurotrophic factor (BDNF) level in an organotypic hippocampal slice culture (OHSC). We then investigated the effects of age and MP diet on the cognitive function of male C57BL/6J (B6) mice. After 8-month dietary supplementation, the MP diet (5000 ppm) significantly attenuated the cognitive impairment associated with anti-inflammation, increasing BDNF level and decreasing p-tau (phospho-tau S202) in older B6 mice. We further applied MP dietary supplementation to triple transgenic Alzheimer's disease (3×Tg-AD) mice from 5 to 13 months old. The MP diet exerted neuroprotective, antioxidative, and anti-inflammatory effects and reduced the A β deposition and p-tau (S202/S262) levels in the hippocampus of 3×Tg-AD mice, which might further attenuate the deficit in spatial memory retrieval. Thus, these results revealed that the multifunctional properties of MP might offer a promising supplementary diet to attenuate cognitive dysfunction in AD.